Analisis Saluran Pemasaran Bahan Olahan Karet (Bokar) Di Kecamatan Mandor Kabupaten Landak - Novira Kusrini, Siswandi, Erlinda Yurisinthae, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
This study aimed to analyze the marketing channels on the traditional’s marketing channel through intermediary traders and to analyze the marketing channel through farmer’s are reviewed from a marketing margin spread, farmer share, and to find out which channels more efficient in Mandor District, Landak Regency. This research shows that the marketing margin in channel II is fewer than channel I and the farmer’s share in channel II is larger than channel I. So this research conclude that the marketing channels II (via farmer’s group) is more efficient compared to the channel I (through intermediary traders) in the Mandor District of Landak regency. On the marketing channel I, the marketing process is still efficient but the farmers receive less price share than in channel II. On the marketting channel II become priority because its more efficient, the farmers receive more profit.Keywords: Marketing rubber, margin, efficiency